Budidaya Organik Kunyit pada Kluster Biofarmaka Kabupaten Karanganyar - Samanhudi, Samanhudi; Yunus, Ahmad; Pujiasmanto, Bambang (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Potential development of medicinal plants in Karanganyar is very large, because this area is famous as a center of medicinal plants such as ginger, turmeric, kencur, and temulawak. In the development of medicinal plants, the approach of organic cultivation is one of the alternatives that can be done to achieve the business. Therefore the application of technology to society about organic farming on Biopharmaca Cluster of Karanganyar was conducted with the aim to apply organic cultivation techniques that have resulted from previous studies, so it can be applied by the community to increase income and welfare. This application of technology to society activity is held in Sambirejo, Jumantono, Karanganyar. The research was conducted from March to October 2016. The results showed that the application of chicken manure affects the number of leaves, number of tillers, and the fresh weight of turmeric rhizome. The addition of manure (chicken, goat, cow) can increase all variables of planting growth which include plant height, number of leaf, number of tillers, fresh weight of plant, dry weight of plant, and fresh weight of rhizomes. Giving three types of manure (chicken, goat, cow) with mycorrhizal dose treatment there is no intraction to some growth observation variables. Mycorrhizal treatment with a dose of 10 g/plant can increase the number of tillers in turmeric. Overall the application of mycorrhizal at various doses (5, 10, and 15 g/plant) can increase plant height, leaf number, number of tillers, and fresh weight of turmeric rhizome.